IL-10 gene promoter and intron polymorphisms and changes in IL-10 secretion in women with idiopathic recurrent miscarriage - Qaddourah, R.H.; Magdoud, K.; Saldanha, F.L.; Mahmood, N.; Mustafa, F.E.; Mahjoub, T.; Almawi, W.Y. (Human reproduction (Oxford), 2014)
STUDY QUESTION Is recurrent pregnancy loss (RPL) associated with polymorphisms in the promoter and intron regions of the interleukin-10 (IL-10) gene? SUMMARY ANSWER IL-10 rs1518111 was found to be associated with RPL but the commonly studied promoter variants rs1800872, rs1800871 and 1800896 were not. WHAT IS KNOWN ALREADY Reduced expression of IL-10 is implicated in RPL, due to defective maternal immune tolerance (causing early miscarriages) or placental vascular insufficiency (causing late losses). IL-10 production is in part inherited, and IL-10 gene variants associated with reduced IL-10 expression have been analyzed for their association with RPL, often with inconclusive results. STUDY DESIGN, SIZE, DURATION A retrospective case–control study was performed between January 2011 and April 2012. The subjects comprised 296 RPL cases and 305 control women. PARTICIPANTS/MATERIALS, SETTING, METHODS Genotyping of the IL-10 intron (rs1878672, rs3024492, rs1554286, rs1518111, rs3024491, rs3024490) and promoter (rs1800872, rs1800871, rs1800896) variants was done by real-time PCR, with defined clusters. MAIN RESULTS AND THE ROLE OF CHANCE A higher minor allele frequency (MAF) of rs1518111 (P = 0.03) was in seen RPL cases; but the MAFs of the remaining SNPs were comparable between cases and controls. Setting the homozygous major allele genotype (1/1) as the reference, significantly higher frequencies of heterozygous rs1554286 and rs1800872, and homozygous rs1800896 genotype carriers, and a reduced frequency of homozygous rs1518111 genotype carriers, were seen in RPL cases, while the distribution of the remaining genotypes were comparable between cases and controls. Serum IL-10 levels were significantly reduced in RPL cases compared with control women (P = 0.002), and this correlated with rs1518111 and rs1800871 genotypes in both groups, and with the rs1800872 genotype among control women. A nine-locus (rs1878672, rs3024492, rs1554286, rs1518111, rs3024491, rs3024490, rs1800872, rs1800871 and rs1800896) haploview analysis demonstrated an increased frequency of haplotype 112112121 in RPL cases, thus conferring a disease susceptibility nature to this haplotype. LIMITATIONS, REASONS FOR CAUTION The main limitation of this study was that it was limited to Bahraini Arabs, thereby necessitating parallel studies of other ethnic groups. Another limitation is the study design, which prompts speculation on whether it is a cause–effect relationship. WIDER IMPLICATIONS OF THE FINDINGS While the lack of association of the various IL-10 promoter variants with RPL was in agreement with reports from varied ethnic groups, this is the first study to confirm the association between IL-10 rs151811 intronic variant and RPL. STUDY FUNDING/COMPETING INTEREST(S) The study was funded by grants from the Arabian Gulf University Research Fund. None of the authors report any competing interests.